2012
DOI: 10.1128/jvi.01207-12
|View full text |Cite
|
Sign up to set email alerts
|

Oral Clarithromycin Enhances Airway Immunoglobulin A (IgA) Immunity through Induction of IgA Class Switching Recombination and B-Cell-Activating Factor of the Tumor Necrosis Factor Family Molecule on Mucosal Dendritic Cells in Mice Infected with Influenza A Virus

Abstract: We previously reported that the macrolide antibiotic clarithromycin (CAM) enhanced the mucosal immune response in pediatric influenza, particularly in children treated with the antiviral neuraminidase inhibitor oseltamivir (OSV) with low production of mucosal antiviral secretory IgA (S-IgA). The aims of the present study were to confirm the effects of CAM on S-IgA immune responses, by using influenza A virus (IAV) H1N1-infected mice treated with or without OSV, and to determine the molecular mechanisms respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
4
30
0
1
Order By: Relevance
“…Subsequently, IgA-committed B cells migrate to mucosal effector tissues including the nasal passages [26]. We reported recently that CAM enhances IgA class switching recombination through upregulation of BAFF in mucosal dendritic cells and activation-induced cytidine deaminase in B cells [14]. The present clinical results add support to these early studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Subsequently, IgA-committed B cells migrate to mucosal effector tissues including the nasal passages [26]. We reported recently that CAM enhances IgA class switching recombination through upregulation of BAFF in mucosal dendritic cells and activation-induced cytidine deaminase in B cells [14]. The present clinical results add support to these early studies.…”
Section: Discussionsupporting
confidence: 82%
“…Of interest, we have also reported that 75% of patients treated with the combination of CAM and OSV show increases in S-IgA production to levels similar to those seen in patients treated with CAM alone and untreated patients. In addition, we recently determined the molecular mechanisms responsible for the enhanced induction of mucosal IgA class switching recombination in CAM-treated mice [14]. The obtained data indicated that CAM significantly enhances the expression levels of B-cell-activating factor of the tumor necrosis factor family (BAFF) molecule on mucosal dendritic cells as well as those of activation-induced cytidine deaminase and Iμ-Cα transcripts on B cells [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation, the cells were fixed with 4% paraformaldehyde in phosphate-buffered saline (-) for 30 min at 4°C and then permeabilized with 0.3% Triton X-100 for 20 min at room temperature. A mouse anti-influenza A NP antibody (FluA-NP 4F1; SouthernBiotech, Birmingham, AL, USA) and horseradish peroxidase-conjugated goat anti-mouse IgG antibody (SouthernBiotech) were used as primary and secondary antibodies, respectively [44]. To visualize the infected cells, TrueBlue peroxidase substrate (KPL, Gaithersburg, MD, USA) was added, and color development was terminated after 15 min of incubation by washing with H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…In order to collect bronchoalveolar lavage fluids (BALF) and tracheal lavage fluids (TLF), these animals were divided into six groups: normal control group-intubation (NC-I), normal control group-nasal drop (NC-D), normal intubation (NI) group, normal nasal drop (ND) group, model intubation (MI) group, and model nasal drop (MD) group. On the 14 th day, tracheal lavage fluids and bronchoalveolar fluids of 5-7 animals in each group were collected and subjected to the enzyme-linked immunosorbent assay (ELISA) to determine secretory IgA[29,30].…”
mentioning
confidence: 99%